Pengaruh Kompensasi Terhadap Loyalitas Karyawan Melalui Komitmen Organisasional (Studi Kasus Pada PT Sambas Alam Lestari) - admin, Gustini B1021161050 (Jurnal Manajemen Update, 2021)
Compensation is a reward given to employees, both financial and non-financial as compensation for sacrifices to the organization. Organizational Commitment is the attitude,feelings and behavior of an individual who sided with the organization and was involved in the process of organizational activities and remained in the organization to achieve organizational goals. Employee Loyalty is employee loyalty to his job, position and the organization where he works. This study aims to examine and analyze the effect of compensation on employee loyalty at PT Sambas Alam Lestari through organizational commitment. This research uses quantitative methods. The population in this study were employee of PT Sambas Alam Lestari. The sample in this study were employees of the production division who had worked for more than 3 years, totaling 83 employees who were determined by non-probability sampling technique in the SPSS 23 program. The results showed that compensation had a positive and significant effect on the organizational commitment of the employees of PT Sambas Alam Lestari. Compensation has a negative and insignificant effect on employee loyalty at PT Sambas Alam Lestari. Compensation variables and organizational commitment in explaining their effect on employee loyalty is 40,8%, while the remaining 59.2% is influenced by other variables outside the research model. Â Keywords: Compensation, Organizational Commitment and Employee LoyaltyDaftar PustakaAdisti, Filda., Musadieq, MA. (2017). Pengaruh Kompensasi Terhadap Motivasi Kerja Dan Loyalitas Karyawan PT Bank Rakyat Indonesia Tbk Cabang Malang. Jurnal Administrasi Bisnis. Vol 50. No 1Allen , N., & Meyer, J. (1991). A three component Conceptualization of Organizational Commitment. Human Resource Management Review. 61-68Ardana, I Komang, dkk. (2012). Manajemen Sumber Daya Manusia. Yogyakarta: Graha IlmuAryanti, Anik. (2016). Pengaruh Kompensasi, Motivasi Kerja dan pengembangan Karir Terhadap Loyalitas Kerja Karyawan PT jasa Marga Persero TBK. Jurnal Pengembangan Wiraswasta. Vol 18. No 3Gouzali, Saydam. (2011). Manajemen Sumber Daya Manusia Jilid 1, Jakarta: Gunung AgungHardianty, Indah. (2014). Pengaruh Karakteristik Pribadi dan Komitmen Organisasi Terhadap Loyalitas Pegawai Negeri Sipil Dinas Perindustrian Perdagangan dan Pengelolaan Pasar Kabupaten Indragiri Hulu. JOM Fekon. Vol 1 (2)Hasibuan, SP Malayu. (2012). Manajemen Sumber Daya Manusia. Edisi Revisi. Jakarta: Bumi AksaraIhwana, Filian Mufcha.,dkk. (2017). Pengaruh Kompensasi dan Motivasi Kerja Terhadap Loyalitas Perawat Magang pada Rumah Sakit Lanud Iswahjudi Maospati Kab.Magetan. Forum Ilmiah Pendidikan Akuntansi.Vol 5. No 1Kreitner, Robert dan Angelo, Kinicki. (2010). Organizational Behaviori. New York:McGraw-HillPratama, EW, dkk . (2016). Pengaruh Kompensasi dan Kepuasan Kerja Terhadap Komitmen Organisasional. Jurnal Administraasi Bisnis. Vol 34 (1)Rahayu, Wilujeng. (2012). Presepsi Keadlian Kompensasi Terhadap Komitmen Organisasional Melalui Kepuasan Kerja. Jurnal Manajemen Strategi Bisnis.Vol 2 No 1.Sari, RM., Riana. IG. (2018). Pengaruh Kompensasi dan Motivasi Kerja Terhadap Komitmen Organisasional di PT. Jenggala Keramik Bali. E-Jurnal Manajemen Unud. Vol 7 (3) 1539-1565. DOI: https://doi.org/10.244843/EJMUNUD.2018.v7.i03.p015.Siagian, Sondang P. (2010). Manajemen Sumber Daya Manusia. Jakarta: Bumi AksaraSuparyadi. (2015). Manajemen Sumber Daya Manusia: Menciptakan Keunggulan Bersaing Berbasis Kompetensi SDM. Â Yogyakarta: CV Andi OffsetZainal, Veithzal Rivai, dkk. (2015). Manajemen Sumber Daya Manusia untuk Perusahaan. Edisi Ketujuh. Jakarta: Raja Gravindo Persada.